2010
DOI: 10.1007/s00432-010-0888-6
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell adhesion molecule isoform 140 declines with rise of WHO grade in human gliomas and serves as indicator for the invasion zone of multiform glioblastomas and brain metastases

Abstract: The expression of NCAM-140 inversely correlates with the WHO grade of human gliomas. The lost expression of NCAM-140 in human glioblastomas and in brain metastases enables the investigation of the brain-tumor interface and the definition of glioblastoma invasion patterns and shows that brain metastases are more invasive than ever thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…Expression of neural cell-adhesion molecule (NCAM) is, for instance, decreased in glioma cells (Andersson et al, 1991;Gratsa et al, 1997;Maidment et al, 1997), and an inverse correlation was found between the expression of one NCAM isoform and the WHOdefined grade of a human glioma cell (Duenisch et al, 2010). NCAM over-expression in tumour astrocytes leads to a significant decrease in their invasive behaviour (Edvardsen et al, 1994;Owens et al, 1998), whereas addition of polysialylated acid (PSA) on NCAM has been shown to facilitate glioma invasion (Suzuki et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of neural cell-adhesion molecule (NCAM) is, for instance, decreased in glioma cells (Andersson et al, 1991;Gratsa et al, 1997;Maidment et al, 1997), and an inverse correlation was found between the expression of one NCAM isoform and the WHOdefined grade of a human glioma cell (Duenisch et al, 2010). NCAM over-expression in tumour astrocytes leads to a significant decrease in their invasive behaviour (Edvardsen et al, 1994;Owens et al, 1998), whereas addition of polysialylated acid (PSA) on NCAM has been shown to facilitate glioma invasion (Suzuki et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Pathologically, GBM has 3 types of infiltration: infiltration with single cells, with cell nests, and with demarcation of a relatively sharp border. 26 Histologically, neoplastic cells have been found in the T2 prolonged regions surrounding GBM. 12,27 Therefore, the peritumoral T2 prolongation of GBM is caused by a combination of vasogenic edema and tumoral infiltration simultaneously.…”
Section: Figmentioning
confidence: 99%
“…More recently, a loss of NCAM expression in gliomas of increasing WHO grade was determined, suggesting that the negative regulation of NCAM is involved in glioma progression. The loss of NCAM expression was also correlated with more diffuse braintumor interfaces (Duenisch et al 2011). Interestingly, NCAM is the major substrate for Poly Sialic Acid (PSA) modifications resulting in PSA-NCAM.…”
Section: Intercellular Interactions Mediate Tumor Cell Invasionmentioning
confidence: 98%